Fitoflagelados potencialmente tóxicos y nocivos de costas del Pacífico mexicano - Bravo-Sierra, Ernesto (2004)
The phytoflagellates are a heterogeneous group of autotrophic, heterotrophic and mixothrophic flagellates of trophic importance in several ecosystems. As in the rest of Latin America, the phytoflagellates that occur in the Mexican Pacific coasts are virtually unknown except for a few records. Their study require complicated collection and analysis methods, a probable cause for the scarce knowledge of this group in tropical and subtropical areas. Material recently collected from various localities along the Mexican Pacific coasts was used to study phytoflagellates, including toxic and potentially toxic species. Plankton samples were treated by gravity and pump filtration, using different methods for fixation and analysis. The phyla Euglenophyta, Heterokontophyta and Haptophyta were found. They occur as plankton in oceanic and shallow coastal waters.